Analysis of The Effect of Volatility, Uncertainty, Complexity, and Ambiguity on The Performance of Culinary Msmes in Enrekang Regency - Zul Rahma Umar; Akhmad Akhmad; Edi Jusriadi; Andi Jam'an; Muchriadi Muchran (Eduvest - Journal of Universal Studies, 2025)
The purpose of this study was to determine and analyze the effect of Volatility, Uncertainty, Complexity, and Ambiguity on the Performance of Culinary MSMEs in Enrekang Regency. The population in this study were culinary MSME players, with data collection techniques through observation, questionnaires and documentation. The data analysis technique uses multiple linear regression analysis. From the results of the research conducted, empirical findings were obtained that volatility has a positive and significant effect on the performance of culinary MSMEs. Uncertainty has a positive and insignificant effect on the performance of culinary MSMEs. Complexity has a positive and significant effect on the performance of culinary MSMEs, and ambiguity has a negative and significant effect on the performance of culinary MSMEs in Enrekang Regency.